Altered exocytosis of inhibitory synaptic vesicles at single presynaptic terminals of cultured striatal neurons in a knock-in mouse model of Huntington’s disease - Xu, Chen; Chen, Sidong; Chen, Xingxiang; Ho, Ka Hei; Park, Chungwon; Yoo, Hanna; Lee, Suk-Ho; Park, Hyokeun (Frontiers in Molecular Neuroscience, 2023)
Huntington’s disease (HD) is a progressive dominantly inherited neurodegenerative disease caused by the expansion of a cytosine-adenine-guanine (CAG) trinucleotide repeat in the huntingtin gene, which encodes the mutant huntingtin protein containing an expanded polyglutamine tract. One of neuropathologic hallmarks of HD is selective degeneration in the striatum. Mechanisms underlying selective neurodegeneration in the striatum of HD remain elusive. Neurodegeneration is suggested to be preceded by abnormal synaptic transmission at the early stage of HD. However, how mutant huntingtin protein affects synaptic vesicle exocytosis at single presynaptic terminals of HD striatal neurons is poorly understood. Here, we measured synaptic vesicle exocytosis at single presynaptic terminals of cultured striatal neurons (mainly inhibitory neurons) in a knock-in mouse model of HD (zQ175) during electrical field stimulation using real-time imaging of FM 1-43 (a lipophilic dye). We found a significant decrease in bouton density and exocytosis of synaptic vesicles at single presynaptic terminals in cultured striatal neurons. Real-time imaging of VGAT-CypHer5E (a pH sensitive dye conjugated to an antibody against vesicular GABA transporter (VGAT)) for inhibitory synaptic vesicles revealed a reduction in bouton density and exocytosis of inhibitory synaptic vesicles at single presynaptic terminals of HD striatal neurons. Thus, our results suggest that the mutant huntingtin protein decreases bouton density and exocytosis of inhibitory synaptic vesicles at single presynaptic terminals of striatal neurons, causing impaired inhibitory synaptic transmission, eventually leading to the neurodegeneration in the striatum of HD.